2010
DOI: 10.4269/ajtmh.2010.09-0423
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for Pleistocene Population Divergence and Expansion of Anopheles albimanus in Southern Central America

Abstract: Abstract. The micro-geographic structure of Anopheles albimanus was studied in southern Central America using partial sequences of the mtDNA cytochrome oxidase subunit I gene (COI). Analysis of molecular variance supported significant genetic structure between populations from Costa Rica and western Panama versus those from centraleastern Panama (Φ CT = 0.33), whereas the within group divergence was shallow and statistically insignificant (Φ ST = 0.08). Furthermore, a statistical parsimony network depicted thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
35
0
3

Year Published

2011
2011
2016
2016

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 34 publications
(38 citation statements)
references
References 53 publications
(98 reference statements)
0
35
0
3
Order By: Relevance
“…68 Few studies on anophelines from South America have determined the presence/ absence of pseudogenes or their influence on the genetic diversity estimates. 57,69 In this study, the analysis conducted to detect numts showed that the high variability detected is caused by genetic differences and not the result of numts co-amplification. [31][32][33] Mitochondrial DNA shows ample signatures of genomic events such as gene flow, migration, bottlenecks, and speciation.…”
Section: Discussionmentioning
confidence: 66%
See 2 more Smart Citations
“…68 Few studies on anophelines from South America have determined the presence/ absence of pseudogenes or their influence on the genetic diversity estimates. 57,69 In this study, the analysis conducted to detect numts showed that the high variability detected is caused by genetic differences and not the result of numts co-amplification. [31][32][33] Mitochondrial DNA shows ample signatures of genomic events such as gene flow, migration, bottlenecks, and speciation.…”
Section: Discussionmentioning
confidence: 66%
“…albimanus (69.2%) 30 and (70.0%). 57 For the diversity measurements, COI sequences from ZAR and BAG were analyzed together because these sites are only 11 km apart and the Nm estimate detected infinite migrants between them. Mutations were all transitions or transversions, resulting in 115 synonymous changes and four amino acid changes.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…28 The sharing of haplotypes across great distances may be the result of isolation, followed by secondary contact in an area known for its complex geologic changes. 68 Pleistocene epoch divergence has been detected for a wide range of insect species, 56, 69 including disease vectors, 28,61,63 suggesting climatic changes as an important force driving the speciation in the Neotropical region. In the present study, the divergence time estimated among all clades and subclades supported diversification during the Pleistocene Epoch.…”
Section: Discussionmentioning
confidence: 99%
“…nuneztovari s.l., as detected in a previous study in this species, 26 and in other anophelines. [61][62][63] The samples from the Amazon Basin tended to have higher genetic diversity, in particular nucleotide diversity, than those from Bolivia/ Colombia/Venezuela. These differences were congruent with those of previous mitochondrial and nuclear gene studies 22,[25][26][27][28]64 and can be indicative of cryptic species, or possibly differences in effective population size ( N e) or other events related to the history of these populations.…”
Section: Discussionmentioning
confidence: 99%